Sales force management - Churchill, Jr., Gilbert A.; Ford, Neil M.; Johnston, Mark W.; Tanner, Jr., John F.; Walker, Jr., Orville C. (Boston : Irwin\McGraw-Hill, 2000)
Business
Includes index
2000-11-01
Keywords: Market management